Financial Literacy and Payment Methods in Enhancing Interest in Cash Waqf: Evidence from UNIDA Gontor - Galih Aisia; Abdul Latif Rizqon; Nurus Shefrilianti Hidayatullah (Universitas Alma Ata, 2025)
Introduction: The development of Islamic philanthropy, especially cash waqf, is gaining momentum in higher education institutions through the support of zakat and waqf management bodies. LAZISWAF UNIDA Gontor plays an important role in providing tuition assistance through waqf funds. However, the factors influencing individuals’ interest in contributing to cash waqf, particularly financial literacy and payment methods, remain underexplored. This study aims to examine (1) the effect of financial literacy on interest in cash waqf, (2) the effect of payment methods on interest in cash waqf, and (3) the combined effect of financial literacy and payment methods on interest in cash waqf at LAZISWAF UNIDA Gontor.Methodology: This study used a quantitative research approach was used with multiple regression analysis. The study involved 132 respondents selected through purposive sampling, comprising students who had knowledge or experience related to cash waqf. Data analysis was conducted using EViews 12 to assess relationships among the independent variables (financial literacy and payment methods) and the dependent variable (interest in cash waqf).Findings/Results: The results show that both financial literacy and payment methods significantly influence interest in cash waqf, both separately and together.Conclusion: A better understanding of waqf principles and the accessibility of digital payment options positively affect individuals' willingness to participate in cash waqf. The theoretical contribution of this study lies in its integrated approach by combining financial literacy and payment method variables to explain interest in cash waqf. This model provides practical insights for Islamic philanthropic institutions to enhance engagement strategies and improve waqf fundraising.